Centromere Identity and the Regulation of Chromosome Segregation - Sundararajan, Kousik; Straight, Aaron F. (Frontiers in Cell and Developmental Biology, 2022)
Eukaryotes segregate their chromosomes during mitosis and meiosis by attaching chromosomes to the microtubules of the spindle so that they can be distributed into daughter cells. The complexity of centromeres ranges from the point centromeres of yeast that attach to a single microtubule to the more complex regional centromeres found in many metazoans or holocentric centromeres of some nematodes, arthropods and plants, that bind to dozens of microtubules per kinetochore. In vertebrates, the centromere is defined by a centromere specific histone variant termed Centromere Protein A (CENP-A) that replaces histone H3 in a subset of centromeric nucleosomes. These CENP-A nucleosomes are distributed on long stretches of highly repetitive DNA and interspersed with histone H3 containing nucleosomes. The mechanisms by which cells control the number and position of CENP-A nucleosomes is unknown but likely important for the organization of centromeric chromatin in mitosis so that the kinetochore is properly oriented for microtubule capture. CENP-A chromatin is epigenetically determined thus cells must correct errors in CENP-A organization to prevent centromere dysfunction and chromosome loss. Recent improvements in sequencing complex centromeres have paved the way for defining the organization of CENP-A nucleosomes in centromeres. Here we discuss the importance and challenges in understanding CENP-A organization and highlight new discoveries and advances enabled by recent improvements in the human genome assembly.